The Chilean Revolts and the Failure of the Constituent Process. - Villalobos‐Ruminott, Sergio (Bulletin of Latin American Research, 2026)
This article aims to contextualise the recent constituent process in Chile and its subsequent failure, paying attention not only to the so‐called contingent nature of the revolts inaugurated in October 2019, but also to the reengineering process implemented by the Pinochet dictatorship. The most ostensible result of this reengineering process was the Constitution of 1980, which was supplemented by a complex juridical‐political framework that has both protected the Constitution and regulated the life of the country during the last 50 years. Despite the recurrence of revolts during the last decades and the aspirations and hopes for a new Constitution, the failure of the recent constituent process is symptomatic of what we can consider the limitations of neoliberal democracy.